Scotland Rising : The Case for Independence. - Hassan, Gerry (London : Pluto Press, 2022)
A systematic exploration of the arguments for Scottish independence from a sympathetic angle.
12. How Scotland Gets an Independence Referendum -- 13. The Next Campaign -- Part V: Future Landscapes -- 14. After an Independence Vote -- 15. The Future of the UK/rUK after Independence -- 16. Scotland's Right to Decide -- 17. Future Stories of Scotland -- Notes -- Index
JSTOR
Keywords: Self-determination, National -- Scotland; Home rule -- Scotland; Scotland -- Politics and government -- 21st century; Droit des peuples à disposer d'eux-mêmes -- Écosse.; Autonomie locale -- Écosse.; Écosse -- Politique et gouvernement -- 21e siècle.; POLITICAL SCIENCE; International Relations; Political Parties; Political Process; Constitutions; Colonialism & Post-Colonialism.; Home rule; Politics and government; Self-determination, National; Scotland; 2000-2099; Electronic books